2013
DOI: 10.1246/cl.130570
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monofluoromethylcyclopropanes from Alkenes without Using Freons: Novel Synthesis of Chlorofluoromethyl Phenyl Sulfide and Its Application in Cyclopropanation

Abstract: Chlorofluoromethyl phenyl sulfide was prepared from the reaction of chloromethyl phenyl sulfide with Selectfluor™. Monofluorocyclopropanation of an alkene was achieved via cyclopropanation using a fluorocarbene derived from the product chlorofluoromethyl phenyl sulfide, followed by oxidation and desulfurization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Considering the few methods available to install the -SCFClH group onto (hetero)arenes, all requiring multistep syntheses and starting from the corresponding thiol, [40][41][42][43] our first objective was to design and prepare a new reagent enabling direct (hetero)aryl-SCFClH bond construction. This would allow for a more facile installation of this motif in a late-stage functionalization context.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the few methods available to install the -SCFClH group onto (hetero)arenes, all requiring multistep syntheses and starting from the corresponding thiol, [40][41][42][43] our first objective was to design and prepare a new reagent enabling direct (hetero)aryl-SCFClH bond construction. This would allow for a more facile installation of this motif in a late-stage functionalization context.…”
Section: Resultsmentioning
confidence: 99%
“…This novel method represents a significant improvement in comparison with known multistep synthetic routes, which are limited to a single example. [40][41][42][43] Having developed a general method for the preparation of ArSCFClH, we investigated the halogen-exchange reaction with widely used [ 18 F]KF/K 222 (Scheme 2). Successful implementation of this protocol would allow access to a novel radiofluorinated motif, thereby expanding the toolbox of reactions available to radiochemists for the design of new probes.…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent the use of Freons as carbene precursors, Kirihara et al reported that monofluorocyclopropanation of alkenes could be achieved from chlorofluoromethyl phenyl sulfide. 16 The sequence involves cyclopropanation, oxidation of the sulfide to the sulfone, and then reductive desulfurization (Scheme 5).…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…Fluoromethylation has recently been investigated, offering a single attachment point for the target substrate . However, fluoromethylene group transfer formally offers two connection points, giving access to monofluorinated 3-membered rings . Along this line, we have recently reported on fluoromethylene transfer from S -monofluoromethyl- S -phenyl-2,3,4,5-tetramethylphenylsulfonium tetrafluoroborate ( 2a ) (Figure ) via ylide intermediate as an alternative to freon (CHFX 2 ) chemistry to access monofluorinated cyclopropane , and epoxide derivatives.…”
Section: Introductionmentioning
confidence: 99%